La théorie des groupes non compétitifs - Daubigney, Jean-Pierre (L'Actualité économique)

(untitled) (HEC Montréal, 1979)
In this paper, the author describes and criticizes the theory of non-competitive groups.According to this theory, the non-competitivity of social groups refers to the existence and the reproduction by heredity of a bi-univocal correspondence between the hierarchy of social groups and the hierarchy of employments. Such a relation comes from the fact that the social origins determine the level of education, the distribution of inborn qualities, and the preference functions of individuals. It is also the result of the demographic reproduction pattern of social groups. In such conditions, the incomes hierarchy is the result as well as the means of the hereditary reproduction of social structure and of non-competitivity.Two basic criticisms can be formulated. First, this theory is unable to justify most of the relation underlying the analysis. Second, the proposed explanation model is unable to account for the contemporary ways of non-competitivity such as indicated by the statistics on social mobility.